Deformation behavior of brittle/ductile multilayered composites under interface constraint effect. (February 2017) - Wu, Hao; Fan, Guohua; Huang, Meng; Geng, Lin; Cui, Xiping; Xie, Honglan
Abstract: A brittle/ductile multilayered composite was designed and fabricated by reaction annealing of pure Ti and Al foils, and comprised alternating α-Ti(Al) layer, α+α2 dual-phase layer, and α2 -Ti3 Al layer. Brittle α2 -Ti3 Al phase is expected to impart high yield strength to the composite, while the ductile α-Ti(Al) phase provides the desired tensile ductility. The role of α+α2 dual-phase layer is to weaken the deformation incompatibility between α-Ti(Al) and α2 -Ti3 Al layers. As expected, tensile tests show a good strength-ductility combination. The real-time tracking of local strain evolution process during the tensile deformation provides a new perspective in understanding the relationship between the microstructure and mechanical properties, by which we found the strength-ductility synergy originates from the constrained crack propagation behavior and strain non-localization imparted by multilayered structure. During the tensile deformation, the local Ti3 Al cracking firstly occurred, and the size of plastic zone at the crack tip was theoretically predicted and experimentally validated. Additionally, a model was proposed to describe the stress/strain transfer path before and after cracking. Graphical abstract: Highlights: The deformation behavior of brittle/ductile multilayered composites was studied in situ. The interface constraint fundamentally changed the deformation behavior of brittle/ductile multilayered composites. A model was proposed to describe the local stress/stain transfer process during the tensile deformation. Our work provided a new perspective from local strain evolution to understand the microstructure/properties relationship.